Colorado day by day - Everett, Derek R. (University Press of Colorado ; History Colorado, 2020)
"This-day-in-history approach to key figures and events that shaped Colorado from the 1690s to the present. A relevant vignette for each day of the calendar year, exploring Colorado's many facets through distilled tales of people, places, events, and trends that shaped, and continue to shape, the region."--